GREEN ECONOMY AS THE NEED OF THE TIME AND THE BASIS OF SUCCESSFUL POST-WAR RECONSTRUCTION OF THE COUNTRY - BILOKINNA, Ilona (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The war in Ukraine has been going on for more than a year, and the damage to the economy, infrastructure, and the environment has been significant and is increasing every day. In parallel with this, Ukraine became a candidate for membership of the European Union and thus determined its future path of development. This means that our state accepts all conditions for the creation of a decarbonized economy in order for the European Union to become climate neutral by 2050. However, the above-mentioned problems create significant obstacles on this path. Therefore, in order to fulfill all the conditions before the European Union and in the future to effectively use resources for the successful recovery of the country, it is necessary to develop the economy in accordance with modern realities. A fairly important aspect of the development of the "green economy" is the annual increase in the use of alternative energy sources, including in the agricultural sector. The state has been working for many years on the creation of acceptable institutional support for the development of renewable energy in Ukraine. A very good example is the energy cooperative in Slavutych, during a power outage, it produced energy and enabled city residents to charge various devices and gadgets. And it showed its efficiency compared to traditional energy sources. Therefore, during the reconstruction of our state, it is necessary to pay enough attention to the creation of an institutional environment for the development of energy cooperatives in communities, because they are able to ensure energy independence and at the same time do not have a negative impact on the environment during energy production. Thanks to the green economy, Ukraine is able to fulfill most of the requirements for the European Union to become its full member. In addition, in order to successfully rebuild our country after the war, it is also necessary to develop a green economy, since we already need innovative methods of building the economy, construction, energy system, restoring the quality of soil, water, air in order to meet the modern needs of the population and fight together with international partners with changes climate.